Development of a simulation code for material analysis using the PIGE technique - Preketes-Sigalas, K.; Lagoyannis, A.; Axiotis, M. (HNPS Advances in Nuclear Physics, 2019)
Particle Induced Gamma ray Emission (PIGE) is a well known and widely used Ion Beam Analysis (IBA) technique for non-destructive material analysis, usually in conjunction with Proton Induced X-ray Emission (PIXE). The main drawback in the applicability of PIGE regarding the quantification of light elements in various heavy element substrates is the need for many reference targets with similar matrices to the one under study, because of the importance of the ion energy loss in the calculations. In order to overcome this problem, an appropriate simulation code that uses as inputs the experimental spectrum and the relevant differential cross sections, with the output being the quantification of the concentration depth profiles of the isotopes of interest is needed. A code like this is currently being developed in C++ and it is compatible with Windows, Linux and Mac.